PENGEMBANGAN PERANGKAT PEMBELAJARAN IPA FISIKA BERBASIS STRATEGI SCAFFOLDING PADA MATERI KALOR DAN PERPINDAHANNYA UNTUK SISWA SMP - Hafiza, Deswita; Zulirfan, Zulirfan; Islami, Nur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The learning tools developed are learning tools based on scaffolding strategies on heat and transfer materials for junior high school students, consisting of Learning Implementation Plans (RPP), Student Worksheets (LKPD), and Learning Outcomes Tests. The purpose of this study was to design and develop physics science learning tools and validate learning tools based on scaffolding strategies on heat and its transfer materials. This type of research is Research and Development (R&D) with a 4D model design. The research instrument used was the RPP validation assessment sheet, LKPD and Learning Outcomes Test which was used by the validator to assess learning tools. Data analysis in this study used descriptive analysis, by calculating the validity score of each learning indicator. Based on the results of the analysis of the validity of the data obtained the average value of the validity of the lesson plan is 3.33 with a very high category. The average validity of the LKPD is 3.36 with a very high category. The average validity of the learning outcomes test is 3.26 with a very high category, so that the overall average of learning tools is 3.31 with a very high category. Thus, the IPA learning tools based on the Scaffolding strategy were declared valid and suitable for use in heat and transfer materials for junior high school students.Keyword: Physics Science Learning Tools, Scaffolding Strategy, Heat and Its Transfer.